PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN PENERIMA LAYANAN SURAT PERINTAH PENCAIRAN DANA PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA METRO - Eka Ubaya Ubaya; Winarti Winarti (e-JKPP, 2018)
One of those associated with the financial management area is the poor quality of the financial management area as part of the classic problems that continue to overshadow the accountability financial management area (Ministry of finance,2014:141). The process of disbursement ditenggarai became one of the causes of the problems of the financial management area (Mardiasmo,2009). Problems of disbursement in the budgets and time inaccuracy can be realized the error document SP2D. The purpose of this research is to know the influence of the quality of the service to the recipient's Kepuasa service on the Agency's financial management and Asset Research Metro City Area using quantitative research design with Samples in the research of 50 people. Results of the study indicate that there is the influence of the quality of public services against publishing service recipient satisfaction warrant disbursement on Regional Assets and Financial management of Metro City As for advice based on the results of research This is the use of Regional financial management system applications in the service of the issuance of the warrant of Disbursement needs to be improved, it should be upgraded again the responsibility of the employees on the Agency's financial management and assets in Metro City Area Warrant service Disbursements, needs to be improved readiness officer on the Agency's financial management and the City Metro Area Asset in serving the recipient Service i.e. Officials Administering finance and financial staff in the service of a warrant The disbursement of funds, needs to be increased again the ability of the officers to give confidence to the recipient of the services that the issuance of a warrant for Disbursement according to the time that has been set out in the operational standards.